Fates of Sec, Tat, and YidC Translocases in Mitochondria and Other Eukaryotic Compartments - Petrů, Markéta; Dohnálek, Vít; Füssy, Zoltán; Doležal, Pavel (Molecular biology and evolution, 2021)
Formation of mitochondria by the conversion of a bacterial endosymbiont was a key moment in the evolution of eukaryotes. It was made possible by outsourcing the endosymbiont's genetic control to the host nucleus, while developing the import machinery for proteins synthesized on cytosolic ribosomes. The original protein export machines of the nascent organelle remained to be repurposed or were completely abandoned. This review follows the evolutionary fates of three prokaryotic inner membrane translocases Sec, Tat, and YidC. Homologs of all three translocases can still be found in current mitochondria, but with different importance for mitochondrial function. Although the mitochondrial YidC homolog, Oxa1, became an omnipresent independent insertase, the other two remained only sporadically present in mitochondria. Only a single substrate is known for the mitochondrial Tat and no function has yet been assigned for the mitochondrial Sec. Finally, this review compares these ancestral mitochondrial proteins with their paralogs operating in the plastids and the endomembrane system.
Keywords: Evolution, Molecular; Mitochondria; molekulární evoluce; membránové transportní proteiny; membrane trafficking; neofunctionalization; proteiny z Escherichia coli; transport proteinů; eukaryogenesis; protein targeting; mitochondrie; Membrane Transport Proteins; Mitochondrial Proteins; Eukaryota; Escherichia coli Proteins; Protein Transport; mitochondriální proteiny